Working Memory Performance is Reduced in Children with Congenital Adrenal Hyperplasia - Browne, Wendy V. (Horm Behav, 2014)
Individuals with classic congenital adrenal hyperplasia (CAH) experience impaired glucocorticoid production and are treated postnatally with glucocorticoids. Prior research with animals and other human populations indicates that glucocorticoids can influence memory, particularly working memory. We tested the hypothesis that children with CAH would show reduced working memory. Children in the United Kingdom, aged 7-11 years, with classical CAH (31 girls, 26 boys) were compared to their unaffected relatives (30 girls, 20 boys) on a test of working memory, the Digit Span test. Vocabulary was also assessed to measure verbal intelligence for control purposes. Children with CAH showed reduced working memory performance compared to controls, on both components of the Digit Span test: p = .008 for Digit Span Forward, and p = .027 for Digit Span Backward, and on a composite score, p = .004. These differences were of moderate size (d = .53 to .70). Similar differences were also seen in a subset of 23 matched pairs of children with CAH and their relatives (d = .78 to .92). There were no group differences on Vocabulary. Glucocorticoid abnormality, including treatment effects, could be responsible for the reduced Digit Span performance in children with CAH. Other factors related to CAH, such as salt-wasting crises, could also be involved. Additional research is needed to identify the cause of the memory reduction, which will help to determine if more rapid diagnosis or more precise glucocorticoid treatment would help prevent memory reduction. Educational interventions might also be considered for children with CAH.